2016
DOI: 10.1002/hup.2515
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in in vitro and in vivo metabolic clearances of the antipsychotic drug olanzapine from non‐smoking and smoking Japanese subjects genotyped for cytochrome P4502D6 and flavincontaining monooxygenase 3

Abstract: Olanzapine clearance was not affected by CYP2D6 or FMO3 genotypes or smoking behavior as a single factor under the present conditions because olanzapine clearance is mediated by multiple enzymes involved in two major and one minor pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The N-oxide can be formed also by CYP2D6 in vitro, but olanzapine metabolism in vivo is not influenced by CYP2D6 genotype [111,112]. Olanzapine Noxide formation in vitro by the FMO3 variant (p.(Glu158Lys;Glu308Gly)) was lower than by the ancestral form, (p.(Glu158;Glu308)) [113].…”
Section: Genetic Variants Of Fmos and Their Effect On Drug Metabolismmentioning
confidence: 96%
See 1 more Smart Citation
“…The N-oxide can be formed also by CYP2D6 in vitro, but olanzapine metabolism in vivo is not influenced by CYP2D6 genotype [111,112]. Olanzapine Noxide formation in vitro by the FMO3 variant (p.(Glu158Lys;Glu308Gly)) was lower than by the ancestral form, (p.(Glu158;Glu308)) [113].…”
Section: Genetic Variants Of Fmos and Their Effect On Drug Metabolismmentioning
confidence: 96%
“…When the influence of this compound variant was examined in vivo the C/D (median dose-adjusted steady-state serum concentration) of olanzapine N-oxide in patients homozygous for (p.(Glu158Lys;Glu308Gly)) was ~50% lower than in individuals heterozygous or homozygous for the ancestral form, but the variant allele had no effect on the plasma concentration of olanzapine [114]. In a study of Japanese, several genotypes of FMO3 and CYPs were found not to be associated with changes in olanzapine clearance, the conclusion being that the drug is subject to multi-pathway metabolism and if one pathway is less effective others compensate [112]. Variants of FMO1 have been shown to alter olanzapine metabolism.…”
Section: Genetic Variants Of Fmos and Their Effect On Drug Metabolismmentioning
confidence: 99%
“…Studies in vivo found that in patients homozygous for p.[(Glu158Lys);(Glu308Gly)], the C/D (mean dose-adjusted steadystate serum concentration) of olanzapine N-oxide was ~50% lower than in those heterozygous or homozygous for the ancestral form, p.[(Glu158);(Glu308)], but that the variant allele had no effect on the plasma concentration of olanzapine (Söderberg et al, 2013). In a study of Japanese, genotypes of CYP2D6 and FMO3 were found not to be associated with the rate of clearance of olanzapine, the conclusion being that the drug is subject to multi-pathway metabolism and if one pathway is less effective then others compensate (Okubo et al, 2016).…”
Section: Effects On Drug Metabolismmentioning
confidence: 99%
“…The main circulating metabolites are desmethylolanzapine and olanzapine-10-glucuronide (Callaghan et al, 1999;Erickson-Ridout et al, 2011;Lu et al, 2016). The conversion to desmethylolanzapine is predominantly catalyzed by CYP1A2, with lesser roles for CYP2D6, CYP2C8, and CYP2C19 (Ereshefsky, 1996;Callaghan et al, 1999;Korprasertthaworn et al, 2015;Okubo et al, 2016). Okubo and colleagues investigated the role of CYP1A2, CYP2D6, and FMO3 in individuals of varying CYP2D6 and FMO3 genotype (Okubo et al, 2016).…”
Section: Olanzapinementioning
confidence: 99%
“…The conversion to desmethylolanzapine is predominantly catalyzed by CYP1A2, with lesser roles for CYP2D6, CYP2C8, and CYP2C19 (Ereshefsky, 1996;Callaghan et al, 1999;Korprasertthaworn et al, 2015;Okubo et al, 2016). Okubo and colleagues investigated the role of CYP1A2, CYP2D6, and FMO3 in individuals of varying CYP2D6 and FMO3 genotype (Okubo et al, 2016). Olanzapine N-demethylation and N-oxygenation were found to be catalyzed by CYP1A2 and CYP2D6, and by CYP2D6 and FMO3, respectively, in experiments using liver microsomes and recombinant enzymes.…”
Section: Olanzapinementioning
confidence: 99%